Determination of Stability Constants of Some Bivalent Metal Complexes of 2-Amino-5-Methoxybenzene Thiol - Bhagchandani, Pushpa; Sharma, Bhavana (Asian Journal of Chemistry, 2010)
The successive stability constants of the complexes of 2-amino-5-methoxybenzene thiol with various bivalent transition metal cations have been determined in (60% V/V) acetone-water mixture at 25 ± 0.1ºC and constant ionic strengh μ = 0.1 M (NaCl) by adopting the pH titration technique of Irving and Rossotti.